(untitled) (Multidisciplinary Journal of Science and Technology, 2026)
This article provides a comprehensive analysis of the theoretical, methodological, and practical issues of vocational guidance for youth in the context of globalization and digital transformation. The study substantiates the effectiveness of using modern psychodiagnostic methods in determining the individual psychological characteristics, interests, and talents of young people. Innovative models of vocational counseling are proposed in response to the changing demands of the labor market, specifically focusing on the impact of "Future Skills" and artificial intelligence on employment.